2017
DOI: 10.1016/j.scitotenv.2017.05.039
|View full text |Cite
|
Sign up to set email alerts
|

An alternative approach to risk rank chemicals on the threat they pose to the aquatic environment

Abstract: This work presents a new and unbiased method of risk ranking chemicals based on the threat they pose to the aquatic environment. The study ranked 12 metals, 23 pesticides, 11 other persistent organic pollutants (POPs), 13 pharmaceuticals, 10 surfactants and similar compounds and 2 nanoparticles (total of 71) of concern against one another by comparing their median UK river water and median ecotoxicity effect concentrations. To complement this, by giving an assessment on potential wildlife impacts, risk ranking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 31 publications
2
60
0
Order By: Relevance
“…For some pharmaceuticals, removal performance from trickling filter WWTP can be less than that from activated sludge (Gardner et al ). However, a recent review of chemicals of concern in United Kingdom rivers has not found any chemical to be of higher risk than the metals (Johnson et al ).…”
Section: Discussionmentioning
confidence: 99%
“…For some pharmaceuticals, removal performance from trickling filter WWTP can be less than that from activated sludge (Gardner et al ). However, a recent review of chemicals of concern in United Kingdom rivers has not found any chemical to be of higher risk than the metals (Johnson et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, it can be stated that the prioritization options are many, that prioritization outcomes are dynamic in space and time, and, hence, that the problem definition phase should be used to define precisely which ranking information is most valuable for selecting an abatement option. Regulatory prioritization used to prospectively steer preventive policies can thus be different from more realized environmental quality-based rankings (Johnson et al 2017).…”
Section: Prioritizationmentioning
confidence: 99%
“…China has also considered a "black list" of high PBT chemicals, being the ones deserving the most attention (Jin et al 2014). To avoid these potential errors, a different risk-ranking method has been proposed where a median or percentile of the ecotoxicity data set is compared against the median or a percentile of the MEC, and this has been recently applied to a range of chemicals in the United Kingdom (Donnachie et al 2014(Donnachie et al , 2016Johnson et al 2017) and in China . Typically, this is linked to the toxicity of the chemical and is based on a predicted-no-effect concentration (PNEC).…”
Section: Introductionmentioning
confidence: 99%
“…Together, both could distort the risk assessment by overlooking the chemical causing the most frequent damage to wildlife. To avoid these potential errors, a different risk-ranking method has been proposed where a median or percentile of the ecotoxicity data set is compared against the median or a percentile of the MEC, and this has been recently applied to a range of chemicals in the United Kingdom (Donnachie et al 2014(Donnachie et al , 2016Johnson et al 2017) and in China . Thus, the ecotoxicity value used in the present study is bounded firmly within the data set and is not a prediction beyond what has been recorded in ecotoxicity testing such as is used to generate a PNEC.…”
Section: Introductionmentioning
confidence: 99%